Pro EJB 3 Java Persistence API - Keith, Mike; Schincariol, Merrick (Apress : Imprint: Apress, 2006)
EJB 3.0 sets a precedent. It has made huge advances in ease of development, and its drastically simplified programming model has been widely acclaimed. Mike Keith, EJB 3.0 co-specification lead, and Merrick Schinariol, reviewer of EJB 3.0, offer unparalleled insight and expertise on the EJB 3.0 persistence specification, in this definitive guide to EJB 3.0 persistence technology. Expect full coverage and examination of the EJB 3.0 spec from these expert authors, including: The EntityManager API The new features of EJB Query Language (EJB QL) Basic and advanced object-relational mapping Advanced topics like concurrency, locking, inheritance, and polymorphism Assuming a basic knowledge of Java, SQL, JDBC, and some J2EE experience, Keith and  Schinariol will teach you EJB 3.0 persistence from the ground up. After reading it, you will have an in-depth understanding of the EJB 3.0 persistence API and how to use it in your applications.